Nuclear import of the DSCAM‐cytoplasmic domain drives signaling capable of inhibiting synapse formation. (11th February 2019) - Sachse, Sonja M; Lievens, Sam; Ribeiro, Luís F; Dascenco, Dan; Masschaele, Delphine; Horré, Katrien; Misbaer, Anke; Vanderroost, Nele; De Smet, Anne Sophie; Salta, Evgenia; Erfurth, Maria‐Luise; Kise, Yoshiaki; et al.
Abstract: DSCAM and DSCAML1 are immunoglobulin and cell adhesion‐type receptors serving important neurodevelopmental functions including control of axon growth, branching, neurite self‐avoidance, and neuronal cell death. The signal transduction mechanisms or effectors of DSCAM receptors, however, remain poorly characterized. We used a human ORFeome library to perform a high‐throughput screen in mammalian cells and identified novel cytoplasmic signaling effector candidates including the Down syndrome kinase Dyrk1a, STAT3, USP21, and SH2D2A. Unexpectedly, we also found that the intracellular domains (ICDs) of DSCAM and DSCAML1 specifically and directly interact with IPO5, a nuclear import protein of the importin beta family, via a conserved nuclear localization signal. The DSCAM ICD is released by γ‐secretase‐dependent cleavage, and both the DSCAM and DSCAML1 ICDs efficiently translocate to the nucleus. Furthermore, RNA sequencing confirms that expression of the DSCAM as well as the DSCAML1 ICDs alone can profoundly alter the expression of genes associated with neuronal differentiation and apoptosis, as well as synapse formation and function. Gain‐of‐function experiments using primary cortical neurons show that increasing the levels of either the DSCAM or the DSCAML1 ICD leads to an impairment of neurite growth. Strikingly, increased expression of either full‐length DSCAM or the DSCAM ICD, but not the DSCAML1 ICD, significantly decreases synapse numbers in primary hippocampal neurons. Taken together, we identified a novel membrane‐to‐nucleus signaling mechanism by which DSCAM receptors can alter the expression of regulators of neuronal differentiation and synapse formation and function. Considering that chromosomal duplications lead to increased DSCAM expression in trisomy 21, our findings may help uncover novel mechanisms contributing to intellectual disability in Down syndrome. Synopsis: A novel membrane‐to‐nucleus signaling mechanism of DSCAMs affects the expression of neuronal target genes. Nuclear enrichment of the cleaved intracellular domain of DSCAM (DSCAM‐ICD) in developing neurons can lead to an impairment of neurite growth and strong decrease of synapse numbers. The DYRK family kinases DYRK1A and DYRK1B, the SH2‐domain adaptor SH2D2A, the Ubiquitin specific peptidase USP21, and the transcription factor STAT3 are novel cytoplasmic binding partners of DSCAM and DSCAML1. The ICDs of DSCAM and DSCAML1 interact with the importin beta IPO5 via a conserved nuclear localization signal. γ‐secretase mediated intra‐membrane cleavage of DSCAM results in the release of the DSCAM ICD and both the DSCAM and DSCAML1 ICDs efficiently translocate to the nucleus. In the nucleus, the DSCAM ICD alters the transcription of several genes involved in neuronal differentiation and synapse formation. Abstract : A novel membrane‐to‐nucleus signaling mechanism of the cell adhesion receptors DSCAM and DSCAML1 affects the expression of neuronal target genes causing reduced neurite growth and decreased synapse formation.